Altstraßenforschung als Archäoprognose Theoretische und methodische Überlegungen zur Wegeforschung am Beispiel Westlicher Bodensee - Rodat, Claudia (Wissenschaftliche Buchgesellschaft (wbg), 2022)
Research into old roads is breaking new ground. Claudia Rodat leaves the well-trodden paths of the classic approach, draws on innovative theories and models, discusses GIS-based forecasting methods and presents new ideas for further research into this exciting element of our cultural landscape.